2010
DOI: 10.1111/j.1469-8986.2010.01043.x
|View full text |Cite
|
Sign up to set email alerts
|

Sigh rate and respiratory variability during mental load and sustained attention

Abstract: Spontaneous breathing consists of substantial correlated variability: Parameters characterizing a breath are correlated with parameters characterizing previous and future breaths. On the basis of dynamic system theory, negative emotion states are predicted to reduce correlated variability whereas sustained attention is expected to reduce total respiratory variability. Both are predicted to evoke sighing. To test this, respiratory variability and sighing were assessed during a baseline, stressful mental arithme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
112
1
2

Year Published

2010
2010
2021
2021

Publication Types

Select...
5
3
1

Relationship

2
7

Authors

Journals

citations
Cited by 122 publications
(125 citation statements)
references
References 39 publications
10
112
1
2
Order By: Relevance
“…An increased respiration frequency during a 1-h low-grade mental stress task in healthy subjects was already found in Nilsen et al (2007). Vlemincx et al (2011) also reported an increased breathing rate during mental stress, although Bernardi et al (2000) in contrast observed a slowing down of respiration frequency. The results also reveal an additional effect of the mental load to the physical load as the respiration frequency was higher during MPT1 compared to PT.…”
Section: Discussionmentioning
confidence: 86%
“…An increased respiration frequency during a 1-h low-grade mental stress task in healthy subjects was already found in Nilsen et al (2007). Vlemincx et al (2011) also reported an increased breathing rate during mental stress, although Bernardi et al (2000) in contrast observed a slowing down of respiration frequency. The results also reveal an additional effect of the mental load to the physical load as the respiration frequency was higher during MPT1 compared to PT.…”
Section: Discussionmentioning
confidence: 86%
“…The use of subject-independent classifiers might also explain why inclusion of respiratory information does not lead to an improvement of the performance of the classifier. It has been demonstrated that stress influences the respiratory pattern, but these conclusions are deduced from within-subject comparisons [6], [14]. On a subject-independent level, this information seems to be insignificant.…”
Section: B Classification In Rest and Stressmentioning
confidence: 99%
“…The data used in this research were measured at the Department of Psychology of the KU Leuven (Leuven, Belgium) in the context of a broader study [6], [7]. The electrocardiogram (ECG, sampling frequency f s = 200 Hz) and respiration (f s = 50 Hz) of 43 healthy students (age: 18-22 years) were recorded using the LifeShirt System (Vivometrics Inc., Ventura, CA).…”
Section: A Datamentioning
confidence: 99%
“…Several studies have shown that physiological noise related to respiration and heart-rate variability correlates with cognitive tasks (Birn et al, 1999;Birn et al, 2009;Ent et al, 2014;Park et al, 2014;Vlemincx et al, 2011) and elicits prolonged negative correlations with BOLD signals -especially in midline areas (Birn et al, 2009;de Munck et al, 2008;Ent et al, 2014;Shmueli et al, 2007). Furthermore, task related changes in physiology can produce BOLD signal changes in vascular networks mimicking neuronal network activations (Bright et al, 2015).…”
Section: Task Related Motion Causing Event Related Effectsmentioning
confidence: 99%